Assessment of Climate Services work by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) - Feinstein, ON (2014)
This assessment of CCAFS work on climate services for farmers (which is part of CCAFS Theme 2, “Adaptation through Managing Climate Risk”), which started in 2011 and is scheduled to end (its first phase) in 2015. The assessment was conducted between September and November 2014 to help CCAFS understand the scope of its initiatives, the partnership strategy, and the effectiveness of its implementation1. During the first phase of this assessment an inception report was prepared and discussed with CCAFS Theme 2 Management Team. In addition to reading documents produced by CCAFS Theme 2, and other relevant literature, judgments by CCAFS staff and external partners on Theme 2’s work and results were sought through a questionnaire (one version for CCAFS staff and internal partners and another version for external partners) and telephone and skype interviews (see Annex 2). The assessment did not include field visits or face to face interviews.